METHODS AND SYSTEMS FOR OPERATING A VEHICLE SUBJECT TO A TRAVEL RESTRICTION - CATRON, Robert; HICKSON, Nicholas; WALKER, Mary Amelia (2023)
Systems and methods of operating a vehicle subject to a travel restriction determine when the vehicle is traveling in an unloaded state; determine a speed of the vehicle when the vehicle is traveling in the unloaded state to produce an actual travel empty speed; compare the actual travel empty speed with an historical travel empty speed for the vehicle; and determine that the vehicle operation is subject to the travel restriction when the actual travel empty speed is less than a predetermined percentile of the historical travel empty speed. When the vehicle operation is not subject to the travel restriction, the systems and methods further evaluate vehicle operation based on an established performance parameter for the vehicle under a normal operating condition; and change a vehicle performance parameter during future vehicle operation based on the evaluation.